Klippel trenaunay syndrome-an obstetric challenge - K., Kanmani; M., Meena; D., Narmadha; A., Geethu V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Klippel Trenaunay Syndrome is a rare congenital disease characterized by triad of extensive cutaneous haemangiomas (most common), venous varicosities and hypertrophy affecting a leg and/or arm on one side. We report two cases of pregnant women with Klippel Trenaunay syndrome of which one patient presented with Kasabach Merritt Syndrome (refractory coagulopathy). 24-year-old primigravida of 29 weeks with KTS presented with bleeding gums for two days. Known case of diabetes, hypothyroid on treatment and treated TB lymphadenopathy. She had hypertrophy with varicosities and haemangiomas on left lower limb and vulvar region. She was treated for thrombocytopenia at 19 weeks gestation with steroids. Laboratory studies revealed thrombocytopenia. Steroids were given as per haematologist opinion for thrombocytopenia. She had emergency caesarean section with platelet transfusion at 35 weeks as per vascular surgeon opinion. Postoperatively she was given anticoagulants and steroids. 28-year-old primigravida of 39 weeks with KTS admitted for safe confinement. She had surgery for haemorrhoids at 14 years of age and had bleeding per rectum two years back. She had hypertrophy of left lower limb and cutaneous nevus in multiple dermatomes on left half of body. Doppler left lower limb shows superficial varicosities. Laboratory studies revealed normal. With multidisciplinary approach, she had elective caesarean in view of primigravida/breech-footling presentation. Post operatively she was given anticoagulants. The success in the management of these patients requires the participation of multidisciplinary approach. The use of prophylactic anticoagulant is generally advised during the pregnancy and postpartum period.